2006
DOI: 10.1002/joc.1443
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐decadal variability in daily rainfall at Durham (UK) since the 1850s

Abstract: Abstract:Records of daily rainfall at Durham (UK) are analysed from 1850 to the present. The most notable wet period is the 1870s, followed by a protracted period of below-average rainfall. Other than the 1870s, summers tended to be much wetter than winters during the latter part of the 19th century. In the 20th century, summers had become drier and winters wetter. To analyse large daily totals, three thresholds, 15, 22.6, and 25 mm, are used. For all three indices, the frequency of large falls was highest fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
22
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 49 publications
6
22
0
Order By: Relevance
“…In winter, in many areas of Europe strong increases of extreme precipitation were recorded (Osborn et al, 2000;Schmidli and Frei, 2000;Schönwiese et al, 2003;Moberg and Jones, 2005;Hundecha and Bárdossy, 2005;Ramos and MartinezCasasnovas, 2006;Burt and Horton, 2007;Trömel and Schönwiese, 2007). In Poland, increasing trends of only one index (5dayT) occurred more often than trends towards a decrease; other indices (90pT, 90pNoD, 95pT and 95pNoD) showed some increasing trends but only at few stations.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In winter, in many areas of Europe strong increases of extreme precipitation were recorded (Osborn et al, 2000;Schmidli and Frei, 2000;Schönwiese et al, 2003;Moberg and Jones, 2005;Hundecha and Bárdossy, 2005;Ramos and MartinezCasasnovas, 2006;Burt and Horton, 2007;Trömel and Schönwiese, 2007). In Poland, increasing trends of only one index (5dayT) occurred more often than trends towards a decrease; other indices (90pT, 90pNoD, 95pT and 95pNoD) showed some increasing trends but only at few stations.…”
Section: Discussionmentioning
confidence: 91%
“…The directions of trends in climatic elements depended not just on the long-term period selected, but also on the season studied. Seasonally focused research on extreme precipitation in Europe reveals increasing trends in the winter season in the central and western parts of the continent (Osborn et al, 2000;Schönwiese et al, 2003;Moberg et al, 2006;Burt and Horton, 2007). On the Iberian Peninsula, contrary to the trends observed elsewhere in Europe, decreasing trends dominate in wintertime (Garcia et al, 2007).…”
Section: Introductionmentioning
confidence: 78%
“…Dates are for those data used in the present study; the records of some stations started earlier than the dates given 2000, since increases in winter rainfall and decreases in summer rainfall are well documented over this time (Osborn et al 2000, Osborn & Hulme 2002, Burt & Horton 2007, Maraun et al 2008. To provide a longer-term perspective, the much longer time series for both Plymouth and Princetown from 1912 to 2000 have also been compared.…”
Section: Discussionmentioning
confidence: 99%
“…However, poor model performance means there is less certainty about summer rainfall, with both increases and decreases in extreme precipitation predicted. There has indeed been a widespread shift in the pattern of UK rainfall towards more heavy falls of rain in winter and fewer in summer in recent decades (Osborn et al 2000, Osborn & Hulme 2002, Burt & Horton 2007, Maraun et al 2008, and these changes are reflected in seasonal rainfall totals. Malby et al (2007) identified a clear change in the seasonality of orographic rainfall in the Lake District of northern England and speculated that this was related to the incidence of higher-intensity events, but otherwise there has been little attention paid to changes in upland rainfall gradients associated with this changing seasonality of heavy rainfall.…”
Section: Introductionmentioning
confidence: 99%
“…This interest in long-term trends in nitrate concentrations matches recent interest in long-term hydrological trends, for example in rainfall (e.g. Burt and Horton, 2007) and streamflow (e.g. Dixon et al, 2006).…”
Section: Introductionmentioning
confidence: 62%